PENGARUH COMPUTER ANXIETY TERHADAP KEAHLIAN DOSEN AKUNTANSI MENGGUNAKAN KOMPUTER - EKO ARIEF SUDARYO; DODDY SETIAWAN (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
This research investigated the influence of computer anxiety to the skill of accounting lecturer in using computer. Computer anxiety is the tendency of people to be difficult, worried or afraid about the use pf Information Technology (computer) now or in the future (Igbaria and Parasuraman, 1989). We use Spearman correlation and Kendall’s taub correlation. Samples of this research are accounting lecturer form State University and Private University in Jakarta, Semarang, Solo, Malang and Surabaya. The result show that computer anxiety has significant negative correlation with the skill of accounting lecturer in using computer. So, the result of this research support the hypothesis suggest that accounting lecturer who has low computer anxiety will show the skill of computer higher than accounting lecturer who has high computer anxiety.